2015
DOI: 10.3389/fimmu.2015.00130
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Protective Immune Responses Against Schistosomiasis haematobium in Hamsters and Mice Using Cysteine Peptidase-Based Vaccine

Abstract: One of the major lessons we learned from the radiation-attenuated cercariae vaccine studies is that protective immunity against schistosomiasis is dependent on the induction of T helper (Th)1-/Th2-related immune responses. Since most schistosome larval and adult-worm-derived molecules used for vaccination uniformly induce a polarized Th1 response, it was essential to include a type 2 immune response-inducing molecule, such as cysteine peptidases, in the vaccine formula. Here, we demonstrate that a single subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 44 publications
3
46
0
Order By: Relevance
“…The mechanism by which papain pretreatment or papain‐based vaccination leads to considerable reduction in challenge S . mansoni and S. haematobium is not elucidated as yet. It was repeatedly reported that immunization of BALB/c and C57BL/6 mice with papain alone induced production of IL‐4, IL‐5 and IL‐13 in draining LN and serum IgG1 and IgE, but not IgM or IgG2b, antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which papain pretreatment or papain‐based vaccination leads to considerable reduction in challenge S . mansoni and S. haematobium is not elucidated as yet. It was repeatedly reported that immunization of BALB/c and C57BL/6 mice with papain alone induced production of IL‐4, IL‐5 and IL‐13 in draining LN and serum IgG1 and IgE, but not IgM or IgG2b, antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The data confirm our findings that documented association of resistance against S . mansoni and S. haematobium challenge infection with type 2 biased‐immunity. Accordingly, type 2 responses are fundamental for resistance against schistosome infection, not only for protection against the parasite‐related immune‐pathology .…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvanted rSjIR reduced fecal eggs in mice by 56–67% [18] while immunization with a monovalent rSjTPI vaccine in buffaloes resulted in up 52% reduction in worm burden. Additionally, a cysteine peptidase-based vaccine and a cocktail of antigens have been tested in single formulations for both S. mansoni and S. haematobium and have shown very promising levels of protection (>70%) in mice [59;60]. In addition, lead candidates, Sm14 and Sm-TSP-2 have also been tested in combination with an additional antigen with the aim of enhancing protection in the murine model but this combinational antigen approach has yielded less than 50–60% reduction in worm burden [6163].…”
Section: Introductionmentioning
confidence: 99%
“…proteases or proteolytic enzymes) are vital to successful parasitism, and facilitate invasion of the host, digestion of host proteins, reproduction, modulation of the host’s physiology [1119] and immune response [14, 20]. Interference with these mechanisms by specific vaccines [21, 22] or drugs may provide therapeutic benefits. Indeed, peptidases are excellent druggable targets [2325] and a large body of literature exists demonstrating the therapeutic benefits of small molecule inhibitors targeting peptidases of schistosomes [2629] and other infectious organisms [3036].…”
Section: Introductionmentioning
confidence: 99%